The limitations of conducting collaborative argumentation when teaching argumentative essays in Malaysian secondary schools - Aireen Aina Bahari; Haddi Junaidi Kussin; Raja Nor Safinas Raja Harun; Misrah Mohamed; Norfaizah Abdul Jobar (Studies in English Language and Education, 2021)
The writing of argumentative essays promotes higher-order thinking skills amongst students regardless of their level of studying only when it involves collaborative argumentation. Hence, argumentation researchers recommend that teachers use group argumentation to teach argumentative essays since Vygotsky’s sociocultural theory believed that group argumentation improves students’ writing skills. The study’s objective is to explore the use of group argumentation during the teaching of argumentative essays in English as a Second Language (ESL) classrooms in Malaysia. Hence, the involvement of practitioners is significant so that the full extent of the problem is known rather than being interpreted solely by researchers. This qualitative study was conducted on nine ESL teachers through convenience sampling. Data was collected through online interviews and analyzed using thematic analysis. The findings demonstrated that ESL teachers did not practice group argumentation when teaching argumentative essays. They resorted to the whole-class discussion instead. Five factors contribute to the negligence of group argumentation in ESL classrooms, that is, time, pressure to deliver curriculum, students’ attitude, students’ speaking skills, and the use of the first language (L1). The findings indicated that it is necessary to promote the teaching of argumentative essay writing using group argumentation as one of the teaching approaches in secondary schools to ensure students reap the benefits of collaborative learning to improve their argumentation skills.